(untitled) (Jurnal Destinasi Pariwisata, 2025)
This study aims to analyze the digital marketing strategies implemented by the management of the Hidden Canyon Beji Guwang tourist attraction and evaluate their effectiveness in increasing tourist visits. The research adopts a descriptive qualitative approach, with data collected through observation, in-depth interviews with key stakeholders, and documentation. The focus is on understanding how digital tools are currently utilized and identifying strategic gaps in implementation. The results indicate that digital marketing efforts at Hidden Canyon are still basic and lack professional structuring. The management relies heavily on social media platforms such as Instagram, Facebook, and TikTok as the primary channels for promotion. However, these platforms are not supported by a clear content strategy, nor are SEO (Search Engine Optimization) and SEM (Search Engine Marketing) effectively applied. Additionally, the official website lacks regular updates and functionality, which limits its role as an informative and persuasive marketing tool. Digital engagement is mostly passive, encouraging visitors to leave Google Reviews, without follow-up efforts to foster an active online community or interactive feedback channels. The SWOT analysis shows that while Hidden Canyon has strong potential due to its unique natural attractions and community support, it also faces significant weaknesses in terms of digital management and competition from better-promoted destinations. The evaluation using the 7C Framework highlights underperformance in areas such as content, community, and context. Based on these findings, the study concludes that the digital marketing strategy of Hidden Canyon needs to be more targeted, integrated, and adaptive to current digital trends. Enhancing digital capabilities and implementing a cohesive online strategy are crucial for improving visibility, engagement, and ultimately increasing tourist visits.